2005
DOI: 10.1164/rccm.200406-837oc
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Inhaled Ultrafine versus Fine Zinc Oxide Particles in Healthy Adults

Abstract: Rationale: Zinc oxide is a common, biologically active constituent of particulate air pollution as well as a workplace toxin. Ultrafine particles (Ͻ 0.1 m diameter) are believed to be more potent than an equal mass of inhaled accumulation mode particles (0.1-1.0 m diameter). Objectives: We compared exposure-response relationships for respiratory, hematologic, and cardiovascular endpoints between ultrafine and accumulation mode zinc oxide particles. Methods: In a human inhalation study, 12 healthy adults inhale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
5
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(81 citation statements)
references
References 24 publications
3
71
5
2
Order By: Relevance
“…Two phases of clearance, a fast phase on the order of days representing mucociliary clearance in the tracheobronchial region and a slow phase on the order of years representing macrophage clearance in the alveolar region were defined. Studying 59 Fe labeled iron oxide dust, Albert and Arnett found that particle clearance rate was dependent on size [39]. When the same dose of 100 μCi was inhaled, clearance of ~47% was measured after 2.4 h for particles with diameters of 1.4-2.3 µm while ~87% of larger particles with diameters of 3.5-4.3 µm cleared after 2 h. Note that in this study and for about half of all studies reviewed, the methods used to characterize the aerosol content were not reported.…”
Section: Controlled Human Volunteer Inhalation Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Two phases of clearance, a fast phase on the order of days representing mucociliary clearance in the tracheobronchial region and a slow phase on the order of years representing macrophage clearance in the alveolar region were defined. Studying 59 Fe labeled iron oxide dust, Albert and Arnett found that particle clearance rate was dependent on size [39]. When the same dose of 100 μCi was inhaled, clearance of ~47% was measured after 2.4 h for particles with diameters of 1.4-2.3 µm while ~87% of larger particles with diameters of 3.5-4.3 µm cleared after 2 h. Note that in this study and for about half of all studies reviewed, the methods used to characterize the aerosol content were not reported.…”
Section: Controlled Human Volunteer Inhalation Studiesmentioning
confidence: 99%
“…The authors are not aware of any published human inhalation studies using iron oxide nanoparticles. However, several controlled human inhalation studies have exposed volunteers to other ultrafine particles [57][58][59][60][61][62][63][64][65][66]. In addition, many human inhalation studies have been conducted using Technegas or 99m Tc labeled ultrafine carbon particles; however, this literature is beyond the scope of this review.…”
Section: Controlled Human Volunteer Inhalation Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Freshly generated zinc oxide can cause an inflammatory response known as fume fever (Beckett et al, 2005).…”
Section: Titanium Dioxide (Tio 2 )mentioning
confidence: 99%
“…However, in the research involving MWF, M.avium has only been detected in one/ two incidences (James et al, 2017). Whereas, the most commonly detected mycobacterial species in MWF are usually from the MCC group (Moore et al, 2000;Khan et al, 2003;Beckett et al, 2005). …”
Section: Discussionmentioning
confidence: 99%